Direct evidence of megamammalcarnivore interaction decoded from bone marks in historical fossil collections from the pampean region - Chichkoyan, Karina Vanesa (2017)
Pleistocene South American megafauna has traditionally attracted the interest of scientists and the popular media alike. However, ecological interactions between the species that inhabited these ecosystems, such as predator-prey relationships or interspecific competition, are poorly known. To this regard, carnivore marks imprinted on the fossil bones of megamammal remains are very useful for deciphering biological activity and, hence, potential interspecific relationships among taxa. In this article, we study historical fossil collections housed in different European and Argentinean museums that were excavated during the 19th and early 20th centuries in the Pampean region, Argentina, in order to detect carnivore marks on bones of megamammals and provide crucial information on the ecological relationships between South American taxa during the Pleistocene. Our results indicate that the long bones of megafauna from the Pampean region (e.g., the Mylodontidae and Toxodontidae families) exhibit carnivore marks. Furthermore, long bones of medium-sized species and indeterminate bones also present punctures, pits, scores and fractures. Members of the large-carnivore guild, such as ursids, canids and even felids, are recognised as the main agents that inflicted the marks. We hypothesize that the analysed carnivore marks represent the last stages of megaherbivore carcass exploitation, suggesting full consumption of these animals by the same or multiple taxa in a hunting and/or scavenging scenario. Moreover, our observations provide novel insights that help further our understanding of the palaeoecological relationships of these unique communities of megamammals.